New Organic Raw Materials for Gilthead Seabream (Sparus aurata) Feeding and the Effects on Growth, Nutritive Parameters, Digestibility, and Histology - Eslam Tefal; Ignacio Jauralde; Ana Tomás-Vidal; Silvia Martínez-Llorens; David S. Peñaranda; Miguel Jover-Cerdá (Fishes, 2023)
A 120-day experiment investigated the new organic raw materials for Gilthead seabream (Sparus aurata) feeding on growth, nutritional parameters, digestibility, and histology. An organic control diet (CON) and three diets with 100% organic raw materials—the rest of rainbow trout, visceral Iberian pig, and insects as a protein source (TRO, IBE, and INS)—were tested. After the experiment, growth, nutritional parameters, digestibility, and histology were measured. The CON diet-fed seabream obtained the highest weight; there was no difference between the experimental diets. The crude protein content was the highest in seabream fed the TRO and INS diets. Crude fat was the highest value observed in the CON diet. High digestibility was observed in seabream-fed IBE and INS diets. Except for EAA methionine (Met), there were no static differences in retention efficiency. The diet with the highest hydrolysis rate was IBE. Diet differences were significant but had the typical healthy liver morphology of seabream. Seabream fed on the TRO and INS diets had shorter distal gut measurements. In conclusion, the full substitution of fishmeal with organic raw materials, including rainbow trout remains, Iberian pig viscera, and insects, offers several benefits in terms of digestibility, histology, and growth performance and may help improve sustainable and healthy aquaculture practices.